Desenvolvimento de um processo de cultivo de células de Drosophila melanogaster S2 em biorreator com agitação induzida por ondas para produção da glicoproteína recombinante do vírus da raiva - Decarli, Monize Caiado (Universidade Federal de São Carlos, 2016)
Although effective, current vaccinations against rabies, one of the most lethal infectious diseases in the world, present security issues of administration and production costs. In this scenario, modern biotechnology has become a source of new alternatives of great interest for vaccine production. The main antigen capable of conferring neutralizing immune response against infection by rabies virus is the glycoprotein of rabies virus (RVGP), which the production by recombinant DNA technology has been developed by researchers at the Viral Immunology Laboratory (LIV) of the Butantan Institute of São Paulo using various expression systems in Drosophila melanogaster S2 cells. One of the latest developments is S2MtRVGP-H-His cell line, obtained by stable transfection with plasmids containing cDNA from other components of RVGP and histidine tag to facilitate purification, both under control of the inducicle metallothionein promoter. This work aims to study the kinetic characteristics of cell growth and production of recombinant glycoprotein rRVGP rabies virus strain of Drosophila melanogaster S2MtRVGP-H-His, in order to evaluate the potential of a bioreactor with agitation induced by waves (Wave) for the scale-up production of rRVGP. The first stage of the study, involving batch cultures in 20 mL Schott bottle with commercial culture medium Sf900-III, allowed us to determine the optimal temperature of cultivation (28ºC), time of induction of expression (72 h), the specific growth rate ranging from 0.022 to 0,034 h-1; maximum cell density 1.82×107 cel.mL-¹ and rRVGP produced from 0.07 to 0.99 μg.mL-1. Based on these results, was started the second part of the study performed in the Single-use Wave bioreactor, involving batch cultures with 650 mL of Sf900-III, with 60% of dissolved oxygen and pH ranging without control from 6.2 to 7.0. The culture in the bioreactor showed maximum specific growth rate of 0,035 h-1, maximum cell density was 1.1×107cel.mL-¹ and RVGP produced 0.85 μg.mL-1. The production of large scale rRVGP with S2MtRVGP-H-His cells using the Wave bioreactor has shown to be viable, reproducible and with high potential to scale-up.
Keywords: Glicoproteína do vírus da raiva; Vacina antirrábica; Proteínas recombinantes; Drosophila melanogaster S2; Glycoprotein of rabies virus; Rabies vaccination; Recombinant proteins; Wave bioreactor; OUTROS